Membrane retention potential of Tachypleus gigas during early embryogenesis - Nelson, Bryan Raveen; John, Akbar; Hwei Zhong, Julia; Khan Chowdhury, Ahmed Jalal (Desalination Publications, 2020)
Investigation on metal ion (Cd2+ and Pb2+) retention within the embryonic shell of Tachypleus gigas embryos was investigated. Inductively coupled plasma optical emission spectrometry was used for metal observations whereas developmental abnormalities were observed using a scanning electron microscope and histology via Harrison-Eosin staining. Metal ions penetrate and regulate between the extra- and embryonic shell environments to cause delayed embryogenesis only in early embryonic stages (Stages-E and DE). Ionic regulation was studied and findings showed that the embryonic shell (ES) was capable of selecting required ions whereas the extra-embryonic shell (EES) having higher retention potential. Throughout the 34 d of exposure, Se2+ was accumulated in the yolk mass (YM). Ionic regulation of embryos was influenced by stocking density and concentration of metabolites. Bioaccumulation factor revealed accumulation potential as EES > ES > YM and thus EES is suitable for biological membrane development. The mechanism of ionic regulation in the ES membrane can be used as a model to design a biological membrane capable of removing metals from polluted waters.